PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS HOTS PADA MATERI BILANGAN DAN OPERASINYA PADA SISWA KELAS IV SD - Komang Desi Ariani; I Made Candiasa; Sariyasa Sariyasa (LPPM Institut Pendidikan Nusantara Global, 2023)
High Order Thinking Skills (HOTS) are one of the important thinking skills for learning mathematics. The importance of HOTS causes teachers to be able to map students' HOTS abilities so they can provide appropriate learning, especially to improve HOTS itself. Therefore we need a HOTS-based assessment instrument so that students' higher-order thinking skills can be measured properly. This study aims to develop a HOTS-based assessment instrument on numbers and their operations for fourth grade elementary school students. The development stage carried out is the preliminary stage, the self-evaluation stage, the formative evaluation stage through expert reviews, one on one, and small group) and field tests. The test instrument used is content validity test with Lawshe's CVR coefficient. Furthermore, item analysis was carried out using Graded Response Model (GRM) analysis. The results of this study indicate that the HOTS mathematical test instrument developed using numbers and their operations in measuring the high-level thinking skills of fourth grade students at SD Gugus V Sukawati achieves predetermined criteria, namely valid and reliable. The test instrument in the form of HOTS math questions which was developed has a valid quality in improving the mathematical high-level thinking of fourth grade students at SD Gugus V Sukawati. This is supported by the validation results of 7 validators who obtained a value of 2.95, which means that the HOTS math questions are in the relevant criteria.